Understanding effective factors affecting brand equity - Bhumiphat Gilitwala; Amit Kumar Nag (Cogent Business & Management, 2022)
The purpose of this research is to know the most effective factor that has a relationship with the brand equity of Disney at Disney shop, DLF Mall, Noida, India. The factors that are tested in this research include brand awareness, brand image, perceived quality, brand association, and brand loyalty. A convenient sampling technique was used to collect data from 400 respondents by using online questionnaires. The questionnaire was sent to the people who had visited Disney shop, DLF Mall, Noida, India. The reliability and validity of various factors affecting the brand equity of Disney were examined by confirmatory factor analysis and structural equation modelling. This research found that brand image has the highest relationship and is able to create brand equity for Disney the most, whereas perceived quality and brand association have a low relationship with the brand equity of Disney. In addition, brand awareness has a negative effect on brand equity with a regression weight of-0.086. This research has implications for the brand equity of Disney. There are five factors that can be related to the brand equity of Disney. These five factors are brand awareness, brand image, perceived quality, brand association and brand loyalty. This research helps to develop an insight about the most important factor having an impact on the brand equity of Disney at Disney shop.
Keywords: 650; brand association; Brand awareness; brand equity; brand image; brand loyalty; Business; Administration and Management; Marketing Management; perceived quality